Estudo comportamental das aferências do núcleo ventral do corpo trapezóide ao primeiro núcleo do circuito neural do reflexo auditivo de sobressalto: núcleo da raiz coclear - Barioni, Nicole Orsi [UNESP] (2015)
The cochlear root neurons (CRN) are the first in the central nervous system to receive the acoustic information. They are in connection with sensory integration centers in the brainstem, particularly the pontine caudal nucleus. The CRN are related with the fundamental neural circuit of the acoustic startle reflex, together with the spiral ganglion neurons, the pontine reticular nucleus and the spinal cord motoneurons. The acoustic startle reflex shows various modulations such as habituation, sensitization, fear potentiation and prepulse inhibition. The modulations of the acoustic startle reflex are important in clinical diagnostics of psychiatric and neurodegenerative illnesses such as schizophrenia and Parkinson's disease. Startle modulations are promoted by influences from several nuclei on the fundamental neural circuit of the startle reflex. The cochlear root nucleus is the least studied nucleus of this circuit. The origins of the afferents to cochlear root neurons and its neurochemical identity remain unclear. Recently was described a new source of afferents to cochlear root neurons, cholinergic and coming from the ventral nucleus of the trapezoid body (VNTB). The neurons of this nucleus receive auditory information directly from the inferior colliculus which take part of the auditory pathway and also participates in the neural circuitry responsible for mediating the prepulse inhibition. Therefore, the inferior colliculus may mediate the prepulse inhibition at the cochlear root level via ventral nucleus of the trapezoid body connection, which would be a short and low latency pathway. However, there are no studies on functional aspects of this connection. We intend to study the role of cholinergic projections from the ventral nucleus of the trapezoid body by selective lesion of this nucleus and behavioral assessment of auditory startle reflex and prepulse inhibition. To achieve the purpose we proposed 3 experimental groups: Control ...